(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This paper examines why state regulation of the economy is necessary and the methods used to achieve it. It begins by explaining market failures, equity, and stability objectives that justify intervention. It then reviews key regulatory methods: competition policy, natural monopoly regulation, environmental instruments, price controls and subsidies, regulatory impact assessment, and public procurement rules. Uzbekistan-specific reforms are highlighted, including privatization and competition law updates. The paper concludes with best-practice principles for effective, transparent, and proportionate regulation.